The Factors Affecting Vowel Pronunciation Errors of Indonesian Senior High School Students - Anggrarini, Natalia; Yoga Prawiro, Indra; Rohmaeni, Cecilia (Panicgogy International Journal, 2023)
The difference in language sound system between English and Bahasa Indonesia could create errors in speaking. The analysis of English pronunciation errors and the factors affecting them are needed to reduce pronunciation errors in EFL Students. This research aims to identify the most frequent error and to know the factor affecting the error in pronouncing English pure vowel sounds made by EFL high school students. Using Descriptive Qualitative research on 27 high school students in Indramayu, one district in Indonesia, the researchers conducted Pronunciation tests and interviews to collect the data. This study reported that the most error that frequently occurred were vowels [æ], [ə], [ɜ:], [ɑ:], and [ʌ]. The factors that affected the vowel pronunciation error were the mother tongue and the amount of exposure. In terms of mother tongue, the students used the Javanese language (one of the dialects in Indonesia) to communicate in daily life. In terms of the amount of exposure, they only got pronunciation exposure only from several sources. This study is expected to make both teachers and students more aware of their pronunciation. This study is limited to the pedagogical practice of the teacher in emphasizing pronunciation in teaching speaking. This becomes essential to investigate to capture the teaching speaking in the classroom in creating more meaningful communication.